Question
upstudy study bank question image url

If \( \sin 27^{\circ}=q \), express each of the following in tems of \( q \) \( \begin{array}{ll}\text { a) } \sin 117^{\circ} & \text { b) } \cos \left(-27^{\circ}\right)\end{array} \)

Ask by Ellis Pearson. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( \sin 117^{\circ} = \sqrt{1 - q^2} \) and \( \cos(-27^{\circ}) = \sqrt{1 - q^2} \).

Solution

To express the given trigonometric functions in terms of \( q = \sin 27^{\circ} \), we'll use fundamental trigonometric identities. ### a) Expressing \( \sin 117^{\circ} \) in terms of \( q \) First, recognize that: \[ 117^{\circ} = 90^{\circ} + 27^{\circ} \] Using the **sine addition formula**: \[ \sin(90^{\circ} + \theta) = \cos \theta \] Letting \( \theta = 27^{\circ} \): \[ \sin 117^{\circ} = \cos 27^{\circ} \] Now, using the **Pythagorean identity**: \[ \sin^2 \theta + \cos^2 \theta = 1 \] Solving for \( \cos \theta \): \[ \cos \theta = \sqrt{1 - \sin^2 \theta} \] Since \( \sin 27^{\circ} = q \) and \( 27^{\circ} \) is in the first quadrant (where cosine is positive): \[ \cos 27^{\circ} = \sqrt{1 - q^2} \] Therefore: \[ \sin 117^{\circ} = \sqrt{1 - q^2} \] ### b) Expressing \( \cos(-27^{\circ}) \) in terms of \( q \) The **cosine function** is even, meaning: \[ \cos(-\theta) = \cos \theta \] Thus: \[ \cos(-27^{\circ}) = \cos 27^{\circ} \] Using the same logic as in part (a): \[ \cos 27^{\circ} = \sqrt{1 - q^2} \] Therefore: \[ \cos(-27^{\circ}) = \sqrt{1 - q^2} \] ### Summary Both expressions in terms of \( q \) are: \[ \boxed{ \begin{aligned} \text{a) } \sin 117^{\circ} &= \sqrt{1 - q^2} \\ \text{b) } \cos(-27^{\circ}) &= \sqrt{1 - q^2} \end{aligned} } \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To express \( \sin 117^{\circ} \) in terms of \( q \), we can use the sine angle addition identity. Notably, \( 117^{\circ} = 90^{\circ} + 27^{\circ} \). Hence, \[ \sin 117^{\circ} = \sin(90^{\circ} + 27^{\circ}) = \cos 27^{\circ}. \] Since we know that \( \cos 27^{\circ} = \sqrt{1 - \sin^2 27^{\circ}} = \sqrt{1 - q^2} \), we can express: \[ \sin 117^{\circ} = \sqrt{1 - q^2}. \] For \( \cos(-27^{\circ}) \), we can utilize the property of cosine being an even function: \[ \cos(-27^{\circ}) = \cos(27^{\circ}). \] Again, knowing that \( \cos 27^{\circ} = \sqrt{1 - \sin^2 27^{\circ}} \), we find: \[ \cos(-27^{\circ}) = \sqrt{1 - q^2}. \] In summary, a) \( \sin 117^{\circ} = \sqrt{1 - q^2} \) b) \( \cos(-27^{\circ}) = \sqrt{1 - q^2} \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy